Lamb Shredded Production and Consumer Acceptance of Floss Roll Bread Products - Sarlina Palimbong; Sekar Wahyuningtyas (Jurnal Penelitian Pertanian Terapan, 2024)
Lamb processing as a culinary choice is less prevalent in Indonesia than processing from similar livestock. Lamb meat also has a nutritional value comparable to that of processed meat. On the other hand, lamb meat is more easily damaged, so it needs to be processed to get a longer shelf life, for example, by making it into shredded lamb. The form of shredded meat is practical, can be enjoyed at any time, and is commonly used as a filling for other food products such as bread. This study aims to determine shredded lamb's chemical characteristics and consumer acceptance of shredded lamb as a filling in floss roll bread products. The test parameters include chemical parameters (moisture content, ash, fat, protein, carbohydrates), with each repeated three times, and sensory parameters (texture, taste, color, aroma, and whole). The data analysis used Anova Oneway for chemical parameters and simple calculations for organoleptic parameters. The results showed the moisture content of lamb shredded meat (4.875%), ash (5.80%), fat (18.86%), protein (10.20%), and carbohydrates (60.27%). The organoleptic test of shredded lamb showed the average preference of the panelists as a whole with a score of (3.8), which was between Neutral-Like. On the floss roll bread, the average favorite of the panelists was a score of (4.2) in the Like – Very Like category. It can be concluded that the value of water, ash, and fat content of lamb shredded meat has met the quality requirements of SNI (1995), except for the protein value. This shredded lamb product has a great chance of having a long shelf life, and its use as a filling on floss roll bread is more acceptable than the assessment of single shredded lamb.